Endogenous interleukin‐6 amplifies interleukin‐17 production and corticoid‐resistance in peripheral T cells from patients with multiple sclerosis. Issue 4 (December 2014) - Ferreira, Thais B.; Hygino, Joana; Barros, Priscila O.; Teixeira, Bruna; Kasahara, Taissa M.; Linhares, Ulisses C.; Lopes, Lana Márcia F.; Vasconcelos, Claudia Cristina F.; Alvarenga, Regina; Wing, Ana Cristina; Andrade, Regis M.; Andrade, Arnaldo F. B.; et al.
Summary Interleukin‐6 (IL‐6) has been implicated in the induction of pathogenic IL‐17‐producing T cells in autoimmune diseases, and studies evaluating the role of this cytokine in T‐cell function in patients with multiple sclerosis (MS) are lacking. Our objective was to evaluate the role of IL‐6 receptor (IL‐6R) signalling on in vitro functional status of T cells from patients with relapsing–remitting MS during clinical remission. Our results demonstrated that, even during the remission phase, activated T cells from patients produce higher levels of IL‐17, and this cytokine was positively correlated with disease severity, as determined by Expanded Disability Status Scale score. In the MS group, the blockade of IL‐6R signalling by anti‐IL‐6R monoclonal antibody reduced IL‐17 production and elevated IL‐10 release by activated CD4+ T cells, but it did not alter the production of these cytokines by activated CD8+ T cells. Blockade of IL‐6R signalling also reduced the ability of monocytes to up‐regulate T helper type 17 phenotype in patients with MS. Finally, both cell proliferation and IL‐17 release by CD4+ and, mainly, CD8+ T cells from patients with MS were less sensitive to hydrocortisone inhibition than control group. Interestingly, IL‐6R signalling blockade restored the ability of hydrocortisone to inhibit both T‐cell proliferation and IL‐17 production. Collectively, these results suggest that IL‐6 might be involved in MS pathogenesis by enhancing IL‐17 production and reducing corticoid inhibitory effects on activated T cells.